The influence of body image on psychological symptomatology in breast cancer women undergoing intervention: a pre-post study - Verri, Veronica; Pepe, Ilaria; Abbatantuono, Chiara; Bottalico, Morena; Semeraro, Cristina; Moschetta, Marco; De Caro, Maria Fara; Taurisano, Paolo; Antonucci, Linda Antonella; Taurino, Alessandro (Frontiers in Psychology, 2024)
Introduction: Body image concerns related to breast cancer surgery may challenge patients’ quality of life and their treatment outcomes, thus representing a key aspect to be assessed in the psycho-oncological settings. The present longitudinal study is aimed to 1) investigate the association between preoperative body image and postoperative psychological symptoms in breast cancer patients; 2) explore the impact of pre-/post-surgery variation in body image on psychological symptomatology. Methods: N=72 women undergoing breast cancer surgery were preoperatively screened (T1) using the Body Uneasiness Test (BUT) and were assessed postoperatively (T2) using the Symptom Checklist-90 Revised (SCL-90-R) and re-administered the BUT. Spearman's correlation was used to investigate the relationship between age, preoperative body image and postoperative psychological symptoms, and variation in body image. To predict post-surgical psychological symptomatology, two separated multiple regression models were used to evaluate preoperative body image and its variation after surgery controlling for covariates (i.e., education; intervention type). P significance was set as .05 for all analyses and adjusted for multiple comparisons. Results: At T1, anxiety in relation to body image scores emerged as the most frequently experienced psychological symptomatology after surgery (all adjusted p<.05). Significant correlations were observed between all SCL-90-R scores at T2 and avoidance behaviors and depersonalization scores at T1. The associations were most significantly strong for somatization, depression, anxiety, and hostility (all adjusted p<.05). However, change in body image between pre- and post-intervention was not associated with psychological symptomatology at T2 (all adjusted p>.05). Pre-surgery body avoidance was significantly associated with post-intervention psychological symptoms (SOMβ=.453, p=.0001; DEPβ=.507, p=.0001; AXβ=.459, p=.0001; HOSβ=.410, p=. 0001). However, increased weight phobia between pre- and post-surgery was statistically associated with increased somatization, anxiety, depression and hostility at T2 (βSOM=.439, p=.0001; βDEP=.454, p=.0001; βANX=.471, p=.0001). Discussion: Overall, pre-/post-intervention body concerns were significantly associated with primary psychological symptoms in breast cancer patients undergoing surgery. Higher levels of body avoidance and weight phobia were significantly associated with the primary psychological dimensions assessed. As body concerns might act as quality-of-life predictors, their evaluation is crucial in fostering patients’ well-being and treatment adherence.